Nationalism and right to secession: New states, identities and global security - Ibánez, Alberto G. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article makes a provocative diagnosis: an unlimited right to secession is incompatible with global peace and progress. In order to overcome such a danger, it offers a practical solution: potential new nations should be subject to a viability test. Should each ethnic, cultural or language group claim their own and independent nation, the globe map would end up divided into 5,000 pieces. It is precisely in times of globalization that stable borders and rationalilty are more than ever necessary, and not only because geostrategic stability is at stake, but because sustainable development and peaceful coexistance are as well.
Keywords: nationalism; secession; desintegration; identity; globalization; minorities; security